Therapeutic plasma exchange in the treatment of severe hypertriglyceridemia: a case report - Carvalho,Tiago J (2018)
Severe hypertriglyceridemia is defined as a serum triglyceride level >885mg/dl. It is an uncommon condition associated with serious complications, mainly acute pancreatitis. Treatment includes lifestyle changes, medical therapy and, more recently, extracorporeal apheresis techniques. Herein, we report a case of severe hypertriglyceridemia managed with therapeutic plasma exchange. Our patient presented with severe upper abdominal pain. Bloodwork showed extremely severe hypertriglyceridemia (14871mg/dl) and hypercholesterolemia (1536mg/dl) with only slight elevation of amylase and lipase and no echographic signs of acute pancreatitis. Two sessions of therapeutic plasma exchange were performed, with a mean 3L of plasma treated per session. The triglyceride levels dropped to 2325mg/dl after the first session and to 1207mg/dl after the second. Medical therapy was started, and the patient was discharged a week later. After 36 months of follow-up she remains stable, with triglyceride levels 427mg/dl. In this case therapeutic plasma exchange was an effective and well tolerated treatment for severe hypertriglyceridemia